Analisis Penjatuhan Hukuman dalam Tindak Pidana Aborsi di Pengadilan Negeri Makassar : Studi Putusan Nomor:1224/Pid.Sus/2022/PN.Mks - Wahid Ramadhan; Andi Rahmah; Andi Tanwir Mappanyukki (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Abortion is prohibited under the Indonesian criminal law system. In fact, it is categorized as a crime against life, regulated by several laws and regulations, including the Criminal Code and the Health Law. Indonesian criminal law defines abortion as